Pengaruh E-WOM, Halal Awareness, Influencer Muslim, dan Lifestyle Halal Terhadap Purchase Decision Fashion Muslim Lokal di Aplikasi Tiktok pada Generasi Z - Nita Puspitasari; Norma Rosyidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the influence of Electronic Word of Mouth (E-WOM), Halal Awareness, Muslim Influencers, and Halal Lifestyle on Purchase Decisions of Local Muslim Fashion on the TikTok App among Generation Z. A quantitative approach was used, collecting data through questionnaires from 150 Generation Z respondents who actively transact on TikTok Shop. The results of the regression analysis showed that E-WOM, Muslim influencers, and halal lifestyle have a positive and significant influence on purchase decisions, while halal awareness has a negative but insignificant influence. These findings indicate that digital recommendations, social influence from influencers, and halal lifestyle play a significant role in shaping Generation Z's purchase decisions. In contrast, halal awareness is not traditionally a major factor in their decisions, reflecting the changing preferences of young consumers who prioritize social aspects and lifestyle trends. The practical implications of this study emphasize the importance of a digital marketing strategy that combines the power of E-WOM and Muslim influencers with contextual and engaging halal value adjustments on the TikTok platform.